Rancangan Program Pelayanan Bimbingan Dan Konseling Dalam Mengatasi Permasalahan Belajar Peserta Didik Pada Kelas XI MIPA di SMA Negeri 5 Padang - Isra Eldasyahri; Besti Nora Dwi Putri; Yasrial Chandra (Departement of Mathematics Education, 2023)
This research is entitled Guidance and Counseling Service Program Design in Overcoming Student Learning Problems in Class XI MIPA at SMA Negeri 5 Padang. Thesis, Guidance and Counseling Study Program, Faculty of Social Sciences and Humanities, Pgri University, West Sumatra, Padang, 2023. This research is motivated by the problems students face while studying. The research aims to describe: students' learning problems in aspects 1.) Lack of enthusiasm for learning 2.) Saturated 3.) Lazy 4.) Procrastinating assignments 5.) Hating teachers. 6.) do not want to ask. As well as designing programs based on the analysis of the problems faced by students. This type of research is descriptive quantitative. The population of this study was 252 students of SMA Negeri 5 Padang. The sampling technique used random sampling technique as many as 72 people. The instrument used is the questionnaire. Data analysis using percentage technique. Based on the results of the study, it was revealed that: 1.) Lack of enthusiasm for learning is in the very high category 2.) Saturation is in the high category 3.) Lazy is in the fairly high category 4.) Procrastinating assignments is in the fairly high category 5.) Hates the teacher is in the very high category. 6.) Do not want to ask is in the high category. The design of the Guidance and Counseling Service Program in Overcoming student learning problems at SMA Negeri 5 Padang in the form of information services with the topic of questioning skills and increasing self-confidence, group guidance with the topic of time management material and bibliotherapy with the topic of learning skills. Based on the results of this study, it is recommended that counseling teachers be able to overcome learning problems by trying out the material designed through this research.